2012
DOI: 10.1097/mbc.0b013e32834cb25b
|View full text |Cite
|
Sign up to set email alerts
|

Thigh-length versus knee-length compression stockings for deep vein thrombosis prophylaxis in the inpatient setting

Abstract: Deep vein thrombosis may be a complication of extended length hospital stays. Immobilized patients, such as patients in the postoperative period, are at particularly high risk of developing a deep vein thrombosis, which can be associated with high levels of morbidity and mortality. Due to this, prevention of deep vein thrombosis is of great importance in the inpatient setting. Compression stockings have proven to play an important role in prophylaxis and may be used in their knee-length or thigh-length variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…In the current study, there were no statistically significant differences in pain, oedema, and satisfaction between the two compression stocking length groups. These results were similar to those of a study suggesting no differences in the potential prevention of deep vein thrombosis according to stocking length [ 18 ]. However, the current study results differ from the results of systematic literature reviews [ 19 , 24 ] demonstrating that thigh-length stockings were preferred and more effective.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, there were no statistically significant differences in pain, oedema, and satisfaction between the two compression stocking length groups. These results were similar to those of a study suggesting no differences in the potential prevention of deep vein thrombosis according to stocking length [ 18 ]. However, the current study results differ from the results of systematic literature reviews [ 19 , 24 ] demonstrating that thigh-length stockings were preferred and more effective.…”
Section: Discussionsupporting
confidence: 91%
“…Most studies incorporating different lengths of compression stockings examined the prevention of deep vein thrombosis. In one study, there were no differences in the prevention of thrombus according to stocking length [ 18 ]. Regarding studies examining ways to prevent deep vein thrombosis, a systematic review showed that thigh-length stockings are preferred and more effective [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As was the case in the results of our study, the efficacies of knee‐length and thigh‐length GCS were reported to be similar in related meta‐analyses and systematic reviews (Loomba et al . , Sajid et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta‐analysis evaluating the efficacy of two GCS in the prophylaxis of DVT, it was reported that no statistical significance had been observed between knee‐length and thigh‐length GCS (Loomba et al . ). And, in systematic review studies, it has been mentioned that both sizes of GCS had similar efficacies (Byrne , Sajid et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation